Preliminary investigation on the human response to patterned chromatic glazing. (1st February 2023) - Liu, Dingming; Kovacs-Biro, Mark Janos; Connelly, Karen; Abd-AlHamid, Fedaa; Wu, Yupeng
Abstract: Daylighting has been associated with improved mood, enhanced morale, increased visual comfort and reduced fatigue. Glazing with varying transmittance, colour or configuration may have significant effects on the quality and quantity of daylight within a building, thus good glazing design has posed significant challenges for building designers. Coloured glazing is broadly applied in modern offices worldwide and many studies have explored the effect of this glazing on human performance. Commonly studied are chromatic glazing typologies which offer a unidirectional shift in the colour of light to either bronze or blue. This alters the spectral ability of the glazing and thus changes the indoor luminous environment. It is reported that although occupants prefer warm light, people perform better under cool light condition. This project aims to implement patterns in chromatic glazing to introduce a two-directional colour distortion to alter the colorimetric characteristics of the glazing, heavily affecting the user's perception and performance in the luminous environment. More specifically, seven different indoor luminous conditions were created using various patterned chromatic glazing (100% CAR Blue, 70% CAR Blue, 30% CAR Blue, neutral clear glazing, 30% CAR Bronze, 70% CAR Bronze, and 100% CAR Bronze) to investigate their effect on human perception using a scaled test room (1:3 scaling) to simulate office working conditions. Both subjective (questionnaire on pleasantness, comfort, alertness) and objective (an achromatic Landolt ring test and a chromatic Landolt ring test) evaluations were carried out for the proposed window conditions. The results suggest that the patterned chromatic glazing conditions create a more desirable luminous indoor environment, as well as a more efficient working environment. The 30% blue and 70% blue glazing improved feelings of visual comfort compared to the 100% blue, whilst retaining the efficiency of task completion. Meanwhile the 30% bronze glazing increased the efficiency of task completion compared to the 100% bronze, whilst retaining the ratings for comfort and pleasantness. This implies that the design of patterned chromatic glazing which introduces the combination of two chromatic glazing may be a feasible solution to improve the indoor luminous environment. Highlights: To introduce chromatic glazing with designed patterns for two-directional colour distortion. To investigate the effects of patterned chromatic glazing on participants' perception. 30% bronze, 30% blue and 70% blue were the most appealing choice by occupants.